Compaction of RNA Duplexes in the Cell. (13th October 2020) - Collauto, Alberto; von Bülow, Sören; Gophane, Dnyaneshwar B.; Saha, Subham; Stelzl, Lukas S.; Hummer, Gerhard; Sigurdsson, Snorri T.; Prisner, Thomas F.
Abstract: The structure and flexibility of RNA depends sensitively on the microenvironment. Using pulsed electron‐electron double‐resonance (PELDOR)/double electron‐electron resonance (DEER) spectroscopy combined with advanced labeling techniques, we show that the structure of double‐stranded RNA (dsRNA) changes upon internalization into Xenopus lævis oocytes. Compared to dilute solution, the dsRNA A‐helix is more compact in cells. We recapitulate this compaction in a densely crowded protein solution. Atomic‐resolution molecular dynamics simulations of dsRNA semi‐quantitatively capture the compaction, and identify non‐specific electrostatic interactions between proteins and dsRNA as a possible driver of this effect. Abstract : A combination of advanced labeling techniques for nucleic acids and in‐cell pulsed electron‐electron double‐resonance spectroscopy reveals compaction of the dsRNA A‐helix inside Xenopus lævis oocytes compared to the dilute solution. Atomic‐resolution molecular dynamics simulations in a dense protein solution semi‐quantitatively capture the compaction, pointing to the molecular interactions involved.